Application of Organizational Culture Education, Employee Engagement, and Organizational Citizenship Behavior to the Performance of Bank Mandiri Employees - Supardi, Supardi (Jurnal Pendidikan Edutama, 2024)
Human resources development in an organization has a strategic influence and role in determining progress and optimizing performance improvements which will have an impact on the survival of the organization. This research aims to test and analyze the application of organizational culture education, employee engagement, and organizational citizenship behavior to the performance of Bank Mandiri KCP Jakarta Muara Karang Dalam employees. The type of research used is explanatory research to explain the influence of one variable on another. The sampling technique used saturated sampling with a sample size of 32 employees. Data analysis includes descriptive analysis, instrument tests, classical assumption tests, and multiple linear regression analysis. The research results show that organizational culture education, employee engagement, and organizational citizenship behavior have a significant effect on the performance of Bank Mandiri employees, both simultaneously and partially. The contribution of the influence of the three independent variables to the performance of Bank Mandiri KCP Jakarta Muara Karang Dalam employees is 67.8%.